PENERAPAN PRODUKSI BERSIH PADA PENGELOLAAN LIMBAH BUDIDAYA JAMUR TIRAM (Pleurotus ostreatus) DI DESA SINDANGSARI, KECAMATAN PABUARAN, KABUPATEN SERANG - Tauny Akbari; Moch Chairul Anwar (Jurnal Kebijakan Pembangunan Daerah, 2022)
The aims of this research are to identify and analyze the application of cleaner production in waste management of oyster mushroom cultivation. Observations were held in one of oyster mushroom cultivation in Sindangsari Village, Pabuaran Subdistrict, Serang District. The research method used to analyze the alternative application of cleaner production was quick scanning of the entire production process of oyster mushroom cultivation. The results of waste identification indicate that some stages of oyster mushroom production process have the potential to cause waste, which are making baglog, boiling and sterilizing planting media, and planting mushroom seeds. Based on the determination of the priority scale for cleaner production options, the results obtained in order of priority on the application of clean production in the oyster mushroom cultivation business, namely (1) utilizing charcoal from combustion residues as fertilizer, (2) processing planting media waste as compost material, (3) reuse of used plastics suitable for use as a baglog, and (4) designing an environmentally friendly combustion furnace. Oyster mushroom cultivators can apply clean production based on the order of priority so that the oyster mushroom cultivation business is not only economically profitable, but also environmentally beneficial. Keywords: Cleaner production, waste management, oyster mushroom cultivation.